Gene expression profile of intramuscular muscle in Nellore cattle with extreme values of fatty acid. (December 2016) - Berton, Mariana; Fonseca, Larissa; Gimenez, Daniela; Utembergue, Bruno; Cesar, Aline; Coutinho, Luiz; de Lemos, Marcos; Aboujaoude, Carolyn; Pereira, Angélica; Silva, Rafael; Stafuzza, Nedenia; Feitosa, Fabieli; et al.
Abstract Background Fatty acid type in beef can be detrimental to human health and has received considerable attention in recent years. The aim of this study was to identify differentially expressed genes inlongissimus thoracis muscle of 48 Nellore young bulls with extreme phenotypes for fatty acid composition of intramuscular fat by RNA-seq technique. Results Differential expression analyses between animals with extreme phenotype for fatty acid composition showed a total of 13 differentially expressed genes for myristic (C14:0), 35 for palmitic (C16:0), 187 for stearic (C18:0), 371 for oleic (C18:1, cis-9), 24 for conjugated linoleic (C18:2 cis-9, trans11, CLA), 89 for linoleic (C18:2 cis-9, 12 n6), and 110 genes for α-linolenic (C18:3 n3) fatty acids. For the respective sums of the individual fatty acids, 51 differentially expressed genes for saturated fatty acids (SFA), 336 for monounsaturated (MUFA), 131 for polyunsaturated (PUFA), 92 for PUFA/SFA ratio, 55 for ω3, 627 for ω6, and 22 for ω6/ω3 ratio were identified. Functional annotation analyses identified several genes associated with fatty acid metabolism, such as those involved in intra and extra-cellular transport of fatty acid synthesis precursors in intramuscular fat oflongissimus thoracis muscle. Some of them must be highlighted, such as:ACSM3 andACSS1 genes, which work as a precursor in fatty acid synthesis;DGAT2 gene that acts in the deposition of saturated fat in the adipose tissue;GPP andLPL genes that support the synthesis of insulin, stimulating both the glucose synthesis and the amino acids entry into the cells; and theBDH1 gene, which is responsible for the synthesis and degradation of ketone bodies used in the synthesis of ATP. Conclusion Several genes related to lipid metabolism and fatty acid composition were identified. These findings must contribute to the elucidation of the genetic basis to improve Nellore meat quality traits, with emphasis on human health. Additionally, it can also contribute to improve the knowledge of fatty acid biosynthesis and the selection of animals with better nutritional quality.